EFEKTIFITAS EDUKASI SARAPAN SEHAT TERHADAP PENGETAHUAN GIZI, FREKUENSI SARAPAN, DAN ASUPAN ENERGI PADA SISWA SEKOLAH DASAR NEGERI BEJI 01 KABUPATEN SEMARANG - Rozanah, Fatharani; Yuniarti, Yuniarti; Susiloretni, Kun Aristiati (JURNAL RISET GIZI, 2017)
Background  : The healthy breakfast educatuon is the education in school about breakfast to a person or group through the learning practice  techniques. Objective  : This study aims to determine the effect of nutritional education on nutritional knowledge, breakfast frequency, and breakfast energy intake in elementary school students Negeri Beji 01 Semarang Regency. Method  : This research is an experiment with randomized pre-post test design control group design. The sample size is 30 students in the treatment group and 30 students in the control group. They are students of grade 2 to 4 primary school with criteria who do not usually breakfast, not in a state of illness, and willing to be a sample. This study was conducted for one month by providing nutritional education usingpower point media and handouts in the treatment group and handout for control group. Results : The results showed that nutrition education can increase nutritional knowledge by 22.7 point score (95% CI 15.9 – 29.3) and increase breakfast frequency equal to of 0.95 times (95% CI 1.29-0,62)higher than the control group. There is noteffect between nutritional education to breakfast energy intake (β = 48.78). Conclusion  : Nutrition education improves nutritional knowledge and breakfast frequency, but does not increase breakfast energy intakein elementary school students.